RESOURCE SHARING AND INFORMATION NETWORKING OFLIBRARIES IN BANGLADESH: A STUDY ON USER SATISFACTION - Mannan, S.M.; Lal Bose, Manik (Malaysian Journal of Library and Information Science, 1998)
An analysis of 25 libraries and 100 users of different categories have been conducted to measure the satisfaction level of users on library networking and resource sharing activities among the major libraries in Bangladesh. The key variables for this study include: the existing status of infrastructures and facilities, collections, mode of subscription of journals, user’s visit to the libraries, availability of services and use of databases. User’s suggestions to improve the library services have also been included.